Progress in Cryptology - LATINCRYPT 2010 First International Conference on Cryptology and Information Security in Latin America, Puebla, Mexico, August 8-11, 2010, Proceedings - Abdalla, Michel; Barreto, Paulo S.L.M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book constitutes the proceedings of the First International Conference on Cryptology and Information Security in Latin America, LATINCRYPT 2010, held in Puebla, Mexico, on August 8-11, 2010. The 19 papers presented together with four invited talks were carefully reviewed and selected from 62 submissions. The topics covered are encryption, elliptic curves, implementation of pairings, implementation of cryptographic algorithms, cryptographic protocols and foundations, cryptanalysis of symmetric primitives, post-quantum cryptography, and side-channel attacks.
Encryption -- Broadcast Encryption with Multiple Trust Authorities -- Security of Sequential Multiple Encryption -- Mediated Traceable Anonymous Encryption -- Elliptic Curves -- Starfish on Strike -- Estimating the Size of the Image of Deterministic Hash Functions to Elliptic Curves -- Implementation of Pairings -- Fixed Argument Pairings -- New Software Speed Records for Cryptographic Pairings -- Implementation of Cryptographic Algorithms -- Accelerating Lattice Reduction with FPGAs -- Efficient Software Implementation of Binary Field Arithmetic Using Vector Instruction Sets -- Cryptographic Protocols and Foundations -- Communication Optimal Multi-valued Asynchronous Broadcast Protocol -- On the Impossibility of Batch Update for Cryptographic Accumulators -- On the Round Complexity of Zero-Knowledge Proofs Based on One-Way Permutations -- Cryptanalysis of Symmetric Primitives -- Message Recovery and Pseudo-preimage Attacks on the Compression Function of Hamsi-256 -- Generic Attacks on Misty Schemes -- Post-Quantum Cryptography -- Cryptanalysis of the Hidden Matrix Cryptosystem -- A Lattice-Based Threshold Ring Signature Scheme -- Side-Channel Attacks -- Defeating Any Secret Cryptography with SCARE Attacks -- How Leaky Is an Extractor? -- Combined Implementation Attack Resistant Exponentiation.
Keywords: Data encryption (Computer science).; Cryptology